Effect of Positive Psychology Interventions on the Quality of Prenatal Care Offered by Midwives: A Field Trial - Fatemeh Shaghaghi; Zahra Abedian; Negar Asgharipour; Habibollah Esmaily; Mohammad Forouhar (Wolters Kluwer Medknow Publications, 2020)
Background: The quality of prenatal care has been recognized as critical to the effectiveness of care in optimizing maternal and child health outcomes. This study examined the effect of positive psychology interventions on the quality of prenatal care offered by midwives. Materials and Methods: This field trial was conducted on 60 midwives working in community health centers in Mashhad, Iran, from September 23, 2015 to March 20, 2016. Initially, centers No. 1 and No. 3 were selected via cluster sampling from among the five healthcare centers of Mashhad. Then, all subsidiaries of these centers were listed and assigned to intervention and control groups through simple random sampling. Thus, 60 midwives were randomly assigned to two equal intervention and control groups. The intervention, based on Seligman's Well-Being Theory, was presented weekly with homework in eight 2-h sessions. Before the interventions and immediately after the intervention, the Oxford Happiness Questionnaire (OHQ) and Ryff's Scales of Psychological Well-Being (SPWB) were completed by the midwives, and the Quality of Prenatal Care Questionnaire (QPCQ) was completed by two pregnant women for each midwife. Results: After the intervention, the mean [Standard Deviation (SD)] score of the overall quality of prenatal care in the intervention group was significantly higher than that of the control group [mean (SD) = 1.51 (0.49) vs. 0.05 (0.21); t43,12= 18.7, p < 0.001]. Conclusions: It seems that improving the well-being of midwives through positive psychology interventions is effective on the quality of prenatal care provided by them.